Profil Kemampuan Berpikir Kreatif Siswa Laki-laki dan Perempuan di Sebuah SMA Negeri Surakarta - Amalia Ulfa1; Marina Ruzyati1; Pujiastuti Pujiastuti1; Safira Medina San1; Baskoro Adi Prayitno2 (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
This research is aimed to know: (1) the creative thinking ability of male and female students at Surakarta State Senior High School; and (2) the difference of creative thinking ability between male and female students at Surakarta State Senior High School. This research uses ex post facto method. The sampling technique uses stratified proportional random sampling. The sample of the study was 36 students, consisting of 18 male students and 18 female students in a Surakarta State Senior High School. The students' creative thinking ability is measured using an essay test developed by Ulfah in 2016. Indicators of creative thinking ability measured include the ability to think fluency, flexibility, originality, and elaboration. The data were analyzed using quantitative descriptive and independent t test, calculation using SPSS vers. 21 with a significance level of 0,05. The results showed the average percentage of students' creative thinking ability of 55.21% in sufficient category. The findings of each indicator are as follows: flexibility of 77.08% in the creative category; originality 35.42% in less creative categories; fluency 72.92% in the creative category; and elaboration 35.92% in less creative categories. Different test results of creative thinking ability between male and female students showed no significant difference.